Agri‑Qur’an dan Ketahanan Pangan: Analisis Kebijakan pada Praktek Living Qur’an di Pesantren Al‑Ittifaq (Bandung) dan At‑Thariq (Garut) - Ecep Ismail (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2026)
Food security remains a strategic national priority, reflected in the 2024–2029 National Medium-Term Development Plan (RPJMN), which emphasises sustainability and food self-reliance. This study examines how Qur’anic principles underpin agricultural practice and contribute to local food security at two pesantren: Al-Ittifaq in Bandung and At-Thariq in Garut. Using transcendental phenomenology, the study draws on in-depth interviews, field observations, and document analysis, with data analysed thematically. Findings at Al-Ittifaq identify core “Living Qur’an” principles guiding agricultural practice: amanah (trustworthiness), anti-israf (anti-waste), isti‘mar al-ardh (stewardship of the earth), and maintenance of mizan (natural balance). At-Thariq emphasises eco-friendly farming and environmental education explicitly grounded in Qur’anic values. Both institutions meet internal food needs and extend benefits to surrounding communities. Al-Ittifaq manages 41 hectares, cultivating 63 vegetable and fruit species and producing an estimated 3.2 metric tons of produce per day; organic outputs supply the santri (students) and surplus is marketed locally. Its operations are supported by a network of 270 alumni farmers and 76 partner pesantren. At-Thariq contributes through community empowerment initiatives that strengthen local food security. Together, these models support RPJMN goals by enhancing agricultural productivity, diversifying local food sources, promoting community-based food institutions, and advancing sustainable circular-economy practices. This study highlights pesantren-based Agri-Qur’an initiatives as viable, culturally grounded contributors to national food-security objectives and suggests their potential for scaling through networks of alumni and inter-pesantren partnerships.